2011
DOI: 10.1523/jneurosci.3805-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quantification at the Single Vesicle Level Reveals That a Subset of Synaptic Vesicle Proteins Are Trafficked with High Precision

Abstract: Protein sorting represents a potential point of regulation in neurotransmission because it dictates the protein composition of synaptic vesicles, the organelle that mediates transmitter release. Although the average number of most vesicle proteins has been estimated using bulk biochemical approaches (Takamori et al., 2006), no information exists on the intervesicle variability of protein number, and thus on the precision with which proteins are sorted to vesicles. To address this, we adapted a single molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 39 publications
10
147
2
Order By: Relevance
“…Synapses lacking synaptobrevin 2 display <1% of wild-type release when stimulated by action potential (AP)-mediated calcium influx (6). Proteomic studies have shown that synaptobrevin 2 is a highly abundant SV protein (7) that is exoendocytically sorted with very high precision (8). Similar observations have been made for other SV proteins, including synaptotagmin and vesicular glutamate transporters (VGLUTs).…”
mentioning
confidence: 80%
“…Synapses lacking synaptobrevin 2 display <1% of wild-type release when stimulated by action potential (AP)-mediated calcium influx (6). Proteomic studies have shown that synaptobrevin 2 is a highly abundant SV protein (7) that is exoendocytically sorted with very high precision (8). Similar observations have been made for other SV proteins, including synaptotagmin and vesicular glutamate transporters (VGLUTs).…”
mentioning
confidence: 80%
“…At the synapse, tight exo-endocytic coupling maintains a pool of neurotransmitter-filled synaptic vesicles. Here, transmembrane cargo recognition is critical as synaptic vesicles have a highly defined protein composition (Takamori et al 2006), and there is a remarkably conserved packaging stoichiometry for some transmembrane proteins within reforming synaptic vesicles (Takamori et al 2006;Mutch et al 2011). Synaptotagmin 1 is a vesicle-associated, Ca 2þ -responsive bilayer fusion regulator and therefore necessarily packaged into each regenerating synaptic vesicle following exocytosis.…”
Section: Distant Relations: M-homology Domain Claspsmentioning
confidence: 99%
“…1F). Second, in a recent study that quantified copy number variability of SV proteins within SV populations, SV2 was found to have the most consistent copy number, with nearly all SVs containing five copies of this protein (Mutch et al, 2011). Third, all experiments were performed at least 2 weeks from infection, at which time EGFP:SV2A expression would have been nearly uniform.…”
Section: Measuring Changes In Sv Pools Sizesmentioning
confidence: 99%